2020
DOI: 10.1177/1535370220940273
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the OGF–OGFr pathway correlates with elevated serum OGF and ocular surface complications in the diabetic rat

Abstract: Diabetes often presents with ocular surface complications including dry eye, keratopathy, and altered sensitivity, along with systemic disorders. A common theme associated with corneal surface defects is decreased cellular proliferation. The opioid growth factor (OGF)–OGF receptor (OGFr) regulatory axis maintains epithelial homeostasis and can be modulated by naltrexone, an opioid receptor antagonist, to block OGF–OGFr interaction and increase cellular replication. Complete blockade using naltrexone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(56 citation statements)
references
References 27 publications
7
49
0
Order By: Relevance
“…However, when the changes in OGF expression following topical application are viewed in concert with serum-based effects of systemic NTX, there is strong evidence that OGF expression is correlated with ocular surface defects. As discussed earlier, 22 systemic insulin does not prevent or protect against dry eye and altered corneal surface sensitivity in T1D, whereas the OGF-OGFr pathway appears to have a significant role. In this study, it was demonstrated that two different methods of establishing receptor blockade of OGF from interaction with OGFr resulted in some level of protection from the ocular surface complications of diabetes.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…However, when the changes in OGF expression following topical application are viewed in concert with serum-based effects of systemic NTX, there is strong evidence that OGF expression is correlated with ocular surface defects. As discussed earlier, 22 systemic insulin does not prevent or protect against dry eye and altered corneal surface sensitivity in T1D, whereas the OGF-OGFr pathway appears to have a significant role. In this study, it was demonstrated that two different methods of establishing receptor blockade of OGF from interaction with OGFr resulted in some level of protection from the ocular surface complications of diabetes.…”
Section: Discussionmentioning
confidence: 79%
“…Body weights and blood glucose levels were monitored periodically throughout the eight-week period. 22 Multiple cohorts of animals were required for systemic and topical NTX studies, and at least 8–15 rats were included in each treatment group. Any rat that did not convert to hyperglycemia within four days following STZ injection was removed from the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The eyes were removed from the orbital cavity, processed and immunohistochemically stained with OGF (Penn State University, 1:200) and OGFr (MyBioSource MBS2124207, 1:150) antibodies as described previously ( 16 ). Frozen corneal sections (6-8 µm) from each group were stained following previously published protocols ( 7 , 11 , 12 , 16 ); control sections were stained with the secondary antibody only (Alexa Flour568; Invitrogen; Thermo Fisher Scientific, Inc.). Stained sections were imaged using a Keyence Scope (KEYENCE, Ltd.) and further quantified using ImageJ 1.8.0_172 (National Institutes of Health) to quantify optical density (OD).…”
Section: Methodsmentioning
confidence: 99%